Financial Sector Assessment : Morocco - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) provides a summary of the policy priorities, and main findings intended to assist the Moroccan authorities in evaluating the country's financial system. It reviews the uneasy trade-off between concerns for stability, and development, suggesting Morocco's macroeconomic policies and practices as a whole tend to err more on the side of the concerns of protecting the economy from external shocks. The cautionary approach to overall reforms has had costs in terms of economic growth and development. But, the approach followed did not leave the financial sector out of the process of reforms, and institutional modernization, which permitted, though uneven, the development of the financial sector, but in turn, not allowed the emergence of clear financial market benchmark prices. The structural challenges facing the Moroccan financial system indicate its financial system focuses on financing the Kingdom's economy, where despite a developed financial institutional infrastructure, financial practices lag behind, with a private financial sector dominated by three conglomerates. Notwithstanding, the commercial banking sector is globally healthy, and growing, but the specialized banking system is in dire straits. The degree of disintermediation away from the banking sector, remains limited, with banking accounting for approximately 60 percent of the overall balance sheet of the financial system, in spite of a pension system that mobilizes significant resources, but is financially imbalanced. It is apparent that the main strength of the system lies in the seemingly, robust health of the private commercial banks. A comprehensive strategy to strengthen the financial system would need to include: resolution of the most troubled state-owned banks; review of current procedures used to cope with problem banks; efforts to address the fragility of non-bank financial institutions; clarification of the role of the public financial institutions; and, reinforcement of financial supervision.